Noemi Gonzalez: capstone - Gonzalez, Noemi, artist (Colorado State University. Libraries, 2023)
The artist's statement: Working primarily with found objects and collage elements, my oil paintings deal with social issues pertaining to race, class, and immigration. I work with an array of found material that is relevant to these issues such as wood or drywall retrieved from construction sites, found imagery from magazine interviews, and personal abandoned family photographs. I see these themes working in conjunction with the process of collaging, sanding away, painting over, concealing, or revealing. Informed and often inspired by personal experiences, my paintings shed light on the complex immigrant experience through the everyday life moments while also surfacing hardships pertaining to race and class. Thus, the work grapples with reconstructing narratives, materials and their context, the found and lost, the past and the present.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting